A downstream molecule of 1, 25-dihydroxyvitamin D3, alpha-1-acid glycoprotein, protects against mouse model of renal fibrosis. Issue 1 (December 2018) - Bi, Jing; Watanabe, Hiroshi; Fujimura, Rui; Nishida, Kento; Nakamura, Ryota; Oshiro, Shun; Imafuku, Tadashi; Komori, Hisakazu; Miyahisa, Masako; Tanaka, Motoko; Matsushita, Kazutaka; Maruyama, Toru
Abstract Renal fibrosis, the characteristic feature of progressive chronic kidney disease, is associated with unremitting renal inflammation. Although it is reported that 1, 25-dihydroxyvitamin D3 (1, 25(OH)2D3), the active form of vitamin D, elicits an anti-renal fibrotic effect, its molecular mechanism is still unknown. In this study, renal fibrosis and inflammation observed in the kidney of unilateral ureteral obstruction (UUO) mice were reduced by the treatment of 1, 25(OH)2D3. The plasma protein level of alpha-1-acid glycoprotein (AGP), a downstream molecule of 1, 25(OH)2D3, was increased following administration of 1, 25(OH)2D3. Additionally, increased mRNA expression ofORM1, an AGP gene, was observed in HepG2 cells and THP-1-derived macrophages that treated with 1, 25(OH)2D3. To investigate the involvement of AGP, exogenous AGP was administered to UUO mice, resulting in attenuated renal fibrosis and inflammation. We also found the mRNA expression of CD163, a monocyte/macrophage marker with anti-inflammatory potential, was increased in THP-1-derived macrophages under stimulus from 1, 25(OH)2D3 or AGP. Moreover, AGP prevented lipopolysaccharide-induced macrophage activation. Thus, AGP could be a key molecule in the protective effect of 1, 25(OH)2D3 against renal fibrosis. Taken together, AGP may replace vitamin D to function as an important immune regulator, offering a novel therapeutic strategy for renal inflammation and fibrosis.